Unfulfilled psychosocial needs of the adolescent siblings of patients with cancer and the identification of the related factors - Masoudifar, Zeynab; Rassouli, Maryam; Ashrafizadeh, Hadis; Fathollah Zadeh, Ensieh; Dadashi, Nasrin; Khanali Mojen, Leila (Frontiers in Psychology, 2022)
Background The diagnosis of cancer in a child is a stressful experience for the entire family, particularly for adolescent or young adult siblings and their psychosocial needs (PSNs) may remain unfulfilled. The aim of the study was to assess the unfulfilled PSNs of the adolescent siblings of patients with cancer in Iran and examine the relationships between demographic and medical variables and PSNs. Methods This descriptive analytical study was conducted in 2019 in seven teaching hospitals in Tehran, Iran. Participants were 188 adolescent siblings of patients with cancer. Sampling was performed consecutively. Data were collected using a demographic and clinical characteristics questionnaire and the Sibling Cancer Needs Instrument (SCNI). To investigate the relationship between demographic variables and the mean score of PSNs subscales, first, the correlation was determined, and afterward, the significant variables were analyzed using multiple linear regression. Results In total, 180 adolescent siblings completed the study. Their mean age was 15.66 ± 2.55 years and the mean summary score of their PSNs was 121.15 ± 32.73. Around 80.60% of adolescents indicated at least one unmet need related to each question. The most common unfulfilled needs of participants were related to the information about sibling’s cancer dimension (INFO) (mean: 2.94 ± 0.79) and the less common unfulfilled needs were related to the practical assistance dimension (UFAM) (mean: 2.38 ± 0.93). Based on the regression coefficients, a significant relationship was observed between the mean summary score of PSNs with the duration of cancer (β = –2.199, p = 0.006) and mother’s age (β = –2.805, p = 0.029). Conclusion The adolescent siblings of patients with cancer have different unfulfilled PSNs, particularly respecting information about their siblings’ cancer and support for emotional coping. Family members and healthcare providers should provide these adolescents with strong informational support and fulfill their needs in order to promote their health and their emotional coping.